PERSPEKTIF HUKUM EKONOMI SYARIAH TENTANG WAKAF UANG DI ERA REVOLUSI INDUSTRI 4.0 - hisam ahyani (J-EBI: Jurnal Ekonomi Bisnis Islam, 2022)
Introduction/Main Objectives: This study aims to determine cash waqf in the view of sharia economic law in the era of the industrial revolution 4.0. Background Problems: The understanding of the Indonesian people regarding cash waqf is still minimal. Even though this waqf has great potential for the welfare of the Indonesian people. Novelty: Regarding research from the perspective of Islamic economic law on cash waqf in the era of the industrial revolution 4.0, no one has researched it. Research Methods: The method used is literature research, qualitative, with statutory, historical, comparative and conceptual approaches and this research is normative. Finding/Results: The view of Shariāh Economics in Indonesia regarding cash waqf is carried out in accordance with Law No.41 / 2004 concerning waqf in which moving objects are in the form of "movable object waqf" which is manifested in the form of money. Conclusion: Waqf money in Indonesia in the era of the Industrial Revolution 4.0 can prosper the economy of the people and also the country. Waqf is positioned as social worship where with waqf in Law no.41 / 2004 concerning waqf article 1 it is explained that waqf is the act of a wakif to separate or give up part of his property to be used forever for worship purposes and also for welfare purposes according to Islamic sharia.